Faktor–Faktor yang Berhubungan dengan Keluhan Gangguan Kulit pada Nelayan - Annissa Annissa; Alvi Annisa (Universitas Faletehan, 2023)
Skin disease is one of the most common diseases found in tropical countries like Indonesia. The incidence of skin diseases in Indonesia is still relatively high and a significant health problem. This study aimed to determine the factors associated with complaints of skin disorders among fishermen. It was conducted from April to June 2022. The research type was descriptive with a cross-sectional design. The respondents were selected by using accidental sampling technique with 50 fishermen as respondents. The data collection technique used interviews and observations with questionnaires and observation sheets as the instruments. The data obtained were in the form of respondent characteristics and factors relating to complaints of skin disorders among fishermen. The data was then analyzed by chi-square test. This study showed that 80% of respondents experienced complaints of skin disorders, 82% of respondents had long years of service, and 96% of respondents wore complete personal protective equipment (PPE), and 56% of respondents had a good personal hygiene. The statistical test results showed years of service (p value 0.782), use of PPE (p value 1.000), personal hygiene (p value 0.198) had no significant relationship to complaints of skin disorders. Fishermen should be given promotion of personal hygiene importance and control to PPE completeness which is used to reduce the risk of experiencing skin disorders complaints.